2021
DOI: 10.1126/sciadv.abi5584
|View full text |Cite
|
Sign up to set email alerts
|

Toughening mechanisms for the attachment of architectured materials: The mechanics of the tendon enthesis

Abstract: Architectured materials offer tailored mechanical properties but are limited in engineering applications due to challenges in maintaining toughness across their attachments. The enthesis connects tendon and bone, two vastly different architectured materials, and exhibits toughness across a wide range of loadings. Understanding the mechanisms by which this is achieved could inform the development of engineered attachments. Integrating experiments, simulations, and previously unexplored imaging that enabled simu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 67 publications
1
34
0
Order By: Relevance
“…Strength, stiffness and toughness decreased dramatically beyond a loading angle of 90°. The model reproduced many of the trends and variations in mechanical behaviour seen in tendon enthesis mechanical testing experiments [33] (electronic supplementary material, figure S1). Additional simulation results, using the range of parameters from table 1, are shown in electronic supplementary material, figure S2.…”
Section: The Balance Between Tendon Enthesis Strength Toughness and Stiffness Varies Across Loading Directionsmentioning
confidence: 61%
See 1 more Smart Citation
“…Strength, stiffness and toughness decreased dramatically beyond a loading angle of 90°. The model reproduced many of the trends and variations in mechanical behaviour seen in tendon enthesis mechanical testing experiments [33] (electronic supplementary material, figure S1). Additional simulation results, using the range of parameters from table 1, are shown in electronic supplementary material, figure S2.…”
Section: The Balance Between Tendon Enthesis Strength Toughness and Stiffness Varies Across Loading Directionsmentioning
confidence: 61%
“…However, this alignment changes dramatically over the course of shoulder motion, with significant consequences for the strength of the attachment [11,14]. We recently applied mercury (II) chloride staining to enable simultaneous imaging of the fibrous and bony architecture of the supraspinatus enthesis in a murine supraspinatus tendon and found that the fibrous architecture, when incorporated into a model of interactions between the tendon and bone, could explain the direction-dependence of strength, stiffness, and toughness at the supraspinatus enthesis [33]. In that work, we studied the response of enthesis tendon fibres wrapped around a semicircular bone ridge, representative of the rotator cuff tendon enthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Tendon has a short toe region in which the stress-strain curve is nonlinear followed by an extensive linear elastic region [43,44]. Further nonlinearity is expected at loads sufficiently high to engage the many hierarchical toughening mechanisms in tendon [30][31][32][33]. Our focus was to study an intermediate range leading to the first stages of suture pullout, in which the tendon is strained beyond the toe region, but significant sliding of tendon fibres and fibrils has not yet begun.…”
Section: (B) Discrete Shear-lag Modelmentioning
confidence: 99%
“…Our own work on these suture 'locking' strategies [26][27][28][29] suggests that they are effective in increasing pullout strength, in part because they harness intrinsic load sharing methods that tendon fibres present over the course of failure [30][31][32][33]. However, the process of failure at a repair site begins before these mechanisms engaged.…”
Section: Introductionmentioning
confidence: 99%
“…However, the cross-sectional areas gradually decreased, while fiber curvature increased [ 17 ]. The stress would peak, theoretically, at the tendon-to-bone interface as a result of observed fiber alignment, implying that there may be a unique mechanism to reduce stress concentration at the tendon-to-bone interface [ 17 , 18 ]. Using a customized confocal microscopy–mechanical loading system, Rossetti et al [ 2 ] found a transitional zone of 500 μm in the tendon-to-bone interface.…”
Section: Structure and Function Of The Tendon-to-bone Interfacementioning
confidence: 99%